Orthopaedics and the COVID-19 pandemic - Paul, Prannoy (International Journal of Research in Orthopaedics, 2020)
The ongoing COVID-19 pandemic has affected healthcare systems across the world in an unprecedented manner. Several healthcare providers are now being recruited for COVID management from their original departments. In addition, reallocation of the available resources and the current economic confinements have forced hospitals worldwide to be restructured in a way so as to provide the best possible care for the patients, while preventing the transmission of coronavirus among patients as well as among healthcare providers.